Erythroderma due to generalized pustular psoriasis in an infant: A case report of a rare condition - Anggatama, Marcella; Rinonce, Hanggoro Tri; Wirohadidjojo, Yohanes Widodo; Danarti, Retno (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Erythroderma is a widespread redness of the skin accompanied by exfoliation that affects over 90% of the body surface. Its presence in infants is clinically important because it can be life-threatening, making it essential for paediatricians and dermatologists to be vigilant. Various skin diseases can cause erythroderma. Timely, accurate identification of the underlying cause results in improved treatment and prognosis. Generalized pustular psoriasis is one of many causes for erythroderma. Nevertheless, this condition is rare in infants, making it challenging to diagnose and treat. The current medical evidence for treatment is primarily derived from case reports rather than clinical trials. Hence, this case report aims to share the authors’ experience in treating infants aged 6 months with erythroderma caused by generalized pustular psoriasis. In our case, the diagnosis was determined by completing the patient's medical history, performing a physical examination, and conducting a histopathological examination. The treatment involved the topical application of moisturizers containing ceramide as well as the systemic administration of steroids and vitamin D. Due to the restricted availability of systemic retinoids, the authors administered steroids in this particular case, resulting in an improved outcome.